Logit modeling of the modulation transfer function (MTF) of metal/film portal detectors - Falco, Tomy (Radiology and oncology (Ljubljana), 2000)
Background. Logit analysis is used to fit measured Modulation Transfer Function (MTF) data of frontmetal/film detectors at megavoltage energies. The detectors consist of double-emulsion portal film placed abutting front metal-plates of Copper or Lead ranging in thickness from 0.39 to 2.40 mm. The MTF data reported by other investigators is also analyzed and authenticates this type of modeling. The logit function predicts the MTF to within experimental uncertainty and the weighted linear regression analysis demonstrates that the fitting is successful with high correlation coefficient:-0.999<-r<--0.995. The logit function parameterizes the MTF with two regression parameters, a and b. These parameters exhibit a linear relationship with the front-plate mass thickness greater than the maximum range of electrons. Conclusions. The logit fitting analysis allows the calculation of the MTF for metal-plates that can be used in the design of the front-end of electronic portal imaging devices.
Keywords: Linear models; Logistic models; Radiographic image enhancement; Radiotherapy, high-energy